2013
DOI: 10.1111/echo.12120
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Outflow Tract Systolic Excursion: A Distinguishing Echocardiographic Finding in Acute Pulmonary Embolism

Abstract: This study demonstrated that measurement of RVOT systolic excursion not only is feasible but also extremely useful in identifying aPE and it is particularly helpful in differentiating it from patients with either mcPH or scPH. This variable might be useful to estimate the global impairment in RV contractility and acute hemodynamic derangement seen in aPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It is well recognized that there are regional characteristics of RV systolic function impairment under acute increase of pressure load. 32 Differences in RV regional EF measured by RT3DE have also been reported in patients with tetralogy of Fallot and pulmonary hypertension. [19][20][21] Experimental studies showed Figure 3.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is well recognized that there are regional characteristics of RV systolic function impairment under acute increase of pressure load. 32 Differences in RV regional EF measured by RT3DE have also been reported in patients with tetralogy of Fallot and pulmonary hypertension. [19][20][21] Experimental studies showed Figure 3.…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest there are different characteristics in RV regional systolic function in different RV compartments. It is well recognized that there are regional characteristics of RV systolic function impairment under acute increase of pressure load . Differences in RV regional EF measured by RT3DE have also been reported in patients with tetralogy of Fallot and pulmonary hypertension .…”
Section: Discussionmentioning
confidence: 92%
“…RVOT-SE is defined as the excursion of the RVOT anterior wall during systolic phase and serves as a novel, simple, and promising parameter for assessment of RV function [ 6]. Previous study demonstrated that RVOT-SE is not only extremely useful but also practicable in identifying acute PE and may aid in the differential diagnosis of chronic pulmonary hypertension [ 23]. More importantly, the lowest values of RVOT-SE are only seen in acute PE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though RVOT-FS is not a conclusive parameter, it offers a vital clue for RV dysfunction and should be confirmed with additional indices obtained by more precise and/or complex techniques (MRI, 3D Echo, strain imaging). Several previous studies have also demonstrated a correlation between RVOT and RV dysfunction 9 and found it as a useful parameter in the diagnosis of RV-related disease such as pulmonary embolism.…”
mentioning
confidence: 87%